The Science-Based Pathways to Understanding False Confessions and Wrongful Convictions - Gudjonsson, Gisli H. (Frontiers in Psychology, 2021)
This review shows that there is now a solid scientific evidence base for the ‘expert’ evaluation of disputed confession cases in judicial proceedings. Real-life cases have driven the science by stimulating research into ‘coercive’ police questioning techniques, psychological vulnerabilities to false confession, and the development and validation of relevant psychometric tests. Mandatory electronic recording of police interviews has helped with identifying the situational and personal ‘risk factors’ involved in false confessions and how these interact. It is the combination of a detailed evaluation and analysis of real-life cases, experimental work, and community (and prison/police station) studies that have greatly advanced the science over the past 40 years. In this review, the story of the development of the science during this ‘golden era’ is told through the three established error pathways to false confessions and wrongful convictions: misclassification, coercion, and contamination. A case study of a major miscarriage of justice is used to highlight the key issues at each stage of the error pathways and it shows the continued resistance of the judiciary to admit mistakes and learn from them. Science is a powerful platform from which to educate the police and judiciary.